2016
DOI: 10.1103/physreva.94.043421
|View full text |Cite
|
Sign up to set email alerts
|

Normal Auger processes with ultrashort x-ray pulses in neon

Abstract: Modern x-ray sources enable the production of coherent x-ray pulses with a pulse duration in the same order as the characteristic lifetimes of core-hole states of atoms and molecules. These pulses enable the manipulation of the core-hole population during Auger decay processes, modifying the lineshape of the electron spectra. In this work, we present a theoretical model to study those effects in Neon. We identify effects in the Auger-photoelectron coincidence spectrum due to the duration and intensity of the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The Auger effect is a common analytical tool of x-ray spectroscopy in surface and material science because it is the major effect determining the dynamics of the atoms and molecules in core-hole states [9]. Recently, the resonant Auger effect induced by intense XFELs has been extensively studied owing to its short duration, in the same order as the characteristic lifetime of core-hole states [10][11][12][13][14][15]. It has demonstrated that the Auger spectra can be modified due to the interplay between radiative and nonradiative decay channels [12].…”
Section: Introductionmentioning
confidence: 99%
“…The Auger effect is a common analytical tool of x-ray spectroscopy in surface and material science because it is the major effect determining the dynamics of the atoms and molecules in core-hole states [9]. Recently, the resonant Auger effect induced by intense XFELs has been extensively studied owing to its short duration, in the same order as the characteristic lifetime of core-hole states [10][11][12][13][14][15]. It has demonstrated that the Auger spectra can be modified due to the interplay between radiative and nonradiative decay channels [12].…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the number of states in the excited superposition excited decreases with the length of the attosecond pulse. In order to understand the underlying mechanism of AICM, we should think about the response of the molecule to the x-ray interaction within a one-step model [25,26] that can be extended to a time-dependent framework [27], in which the final dication state excitation depends on the amount of energy pumped into the system. See appendix A for more details about the underlying mechanism.…”
Section: Bmentioning
confidence: 99%